Wing morph- and age-related differences in fertilization success of adult males of a flightless bug, Pyrrhocoris apterus (Heteroptera: Pyrrhocoridae) - Radomír SOCHA (European Journal of Entomology, 2008)
The aim of the present study was to test the hypothesis that short-winged (brachypterous) and long-winged (macropterous) adult males of a flightless bug Pyrrhocoris apterus differ in fertilization success. For this purpose, 5, 10 and 28 days old brachypterous and macropterous males were mated for the same period of time with reproductively active 5 days old brachypterous females. The average hatchability of five egg batches of these females was used as a measure of the fertilization success of the males. The results revealed significantly higher hatchability of the eggs laid by females that copulated with 5 or 10 days old brachypterous males than with same-aged macropterous males. In contrast, the average hatchability of eggs of females that copulated with 28 days old brachypterous males was significantly lower than of those mated with same-aged macropterous males. It is the first report of wing morph- and age-related differences in fertilization success of males in insects with a non-functional wing-polymorphism. The possible relationship between wing- and age-related differential fertilization and the mating success of P. apterus males, and differences in the amount of secretion transferred from their accessory glands into the reproductive tract of females during copulation, is discussed.